2019
DOI: 10.5858/arpa.2018-0353-rs
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell Sarcoma of the Kidney

Abstract: Clear cell sarcoma of the kidney is an uncommon malignant pediatric renal neoplasm that typically presents in the 2- to 3-year age group and has a propensity for aggressive behavior and late relapses. Histologically, this tumor exhibits a great diversity of morphologic patterns that can mimic most other pediatric renal neoplasms, often leading to confusion and misdiagnosis. Until recently, adjunct immunohistochemical and molecular genetic tests to support the diagnosis were lacking. The presence of internal ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…Of the 17 adult CCSK patients, 11 had immunohistochemistry data. Ten cases stained positive for vimentin, which is consistent with most literature ( 12 , 13 ). In fact, vimentin positivity is a strong pathological characteristic of CCSK.…”
Section: Discussionsupporting
confidence: 91%
“…Of the 17 adult CCSK patients, 11 had immunohistochemistry data. Ten cases stained positive for vimentin, which is consistent with most literature ( 12 , 13 ). In fact, vimentin positivity is a strong pathological characteristic of CCSK.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that BCOR family tumours show substantial morphological overlap, 1,15 and delicate capillary networks were observed not only in BCS, but also in other BCOR mutant tumours such as clear cell sarcoma of the kidney. [15][16][17][18] Tumour cell clusters with thin and delicate vascular cores and tiny vascular fragments of BCS may reflect the cytopathological features of BCOR mutant tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Our cases were older, in the fifth decade, and both presented with synchronous pulmonary metastases at diagnosis. As CCSK are known to evolve with very long‐term pulmonary and bone metastasis [ 39 ], it was tempting to document these bone/pulmonary tumours as metastases from an occult CCSK. We found no argument in the medical records arguing in favour of this hypothesis.…”
Section: Discussionmentioning
confidence: 99%